Autistic Disorder - Heidi Liss Radunovich (EDIS)
FCS-2273, a 4-page fact sheet by Heidi Liss Radunovich, describes this disorder for parents, how it is diagnosed, how common it is, what causes it, what parents should do if they think their child has autistic disorder, and how it impacts families. Includes list of internet resources and references. Published by the UF Department of Family Youth and Community Sciences, June 2007.